Learners in Transition Chinese Students' Journeys from EFL to ESL and EIL - FONG, YOKE SIM (Taylor & Francis, 2019)
As the number of Chinese students learning English increases worldwide, the need for teachers to understand the characteristics and challenges facing this group of learners grows. This is particularly true for those students moving from an English as a Foreign Language context to an English as a Second Language/International Language one where they experience academic, linguistic and sociocultural transitions. Drawing on over 20 years' experience teaching English courses to Chinese learners, the author aims to highlight key findings to aid understanding, improve teachers' practice and offer pedagogical recommendations. Using students' voices, the book covers: how the traditional Chinese culture of learning plays a role; how new learning contexts provide opportunities and empowerment; how learners' beliefs and strategies are interconnected; how their motivation and identity underscore the power of real and imagined communities, and finally, that affect matters, showing how learners are propelled by the trajectory of their emotions. The book cites from the rich data collected over a five-year period to authenticate the findings and recommendations but also to give voice to this group of learners to challenge the stereotype of the passive "Chinese learner". The essential insights contained within are useful for pre- and in-service teachers of English and researchers interested in language education around the world.